Estudio comparativo de las tres topologías clásicas de los inversores multinivel controlados mediante modulación SPWM y un motor de inducción tipo jaula de ardilla como carga. - Guerrero Moreta, Fernando Marcelo (2021)
Inverters over time have been and are currently employed in industry for the conversion of direct current to alternating current. Conventional inverters that are mostly used have drawbacks such as low sine output voltage with high harmonic content. Multilevel inverters have become increasingly interested in DC-AC conversion, since, with an appropriate modulation technique, they provide a multi-level output voltage signal (similar to sine wave) with reduced harmonic content and with better efficiency compared to conventional inverters. This research project presents a comparative study of the three classic topologies of multilevel inverters, Diode Clamped, Flying Capacitor and Cascaded H-Bridge of 5 levels, applying a sine pulse width modulation technique (SPWM) and a squirrel cage induction motor as load to determine which topology presents greater feasibility for its future implementation. This is done by establishing a weighted weight table that considers both technical and economic parameters: voltage and current THD, machine behavior (speed and torque), modulation complexity, scalability, number of elements and costs. To this end, Simulink-Matlab simulation software has been used for the design of the power circuit of each topology and the SPWM control circuit, which is based on the comparison of a reference signal or fundamental frequency modulator with a high frequency carrier signal to obtain the control signals required to form the desired voltage levels at the inverter output. After analyzing and comparing the results obtained in the simulation of each of the topologies using the table of weights weighted, it was determined that the inverter capacitors floating 5 levels in comparison with the other two topologies has a lower percentage of THD of supply current and a better behavior on the part of the induction motor, in addition to representing a lower cost because it requires a smaller number of elements, concluding that this topology is the most feasible for future implementation.